（＋）-Tartaric Acid-Catalyzed High Regio- and Stereoselective Aminobromination of Olefins - 陈战国 魏俊发 李文丽 王芸 赵朋飞 石先莹 (Chinese journal of chemistry, 2011)
（＋）-Tartaric acid-catalyzed aminobromination of α,β-unsaturated ketones, α,β-unsaturated esters and simple olefins utilizing TsNHJNBS as the nitrogen/halogen sources at room temperature without protection of inert gases achieved good yields （up to 92% yield） of vicinal haloamino products with excellent regio- and stereoselectivity, even just 10% of （＋）-tartaric acid was used as catalyst. The regio- and stereochemistry was unambiguously confirmed by X-ray structural analysis of products 2b and 12e. The electron-rich and deficient olefins show significant differences in activity to the aminobromination reaction and give the opposite regioselectivities. The 21 cases have been investigated which indicated that our protocol has the advantage of a large scope of olefins. Additionally, tartaric acid as catalyst has the advantage of avoiding any hazardous metals retained in products.